Udgravningen i Perlegade og Sønderborgs historie i middelalderen - Berg, Christina (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
In 2020, two houses burned down on Perlegade 21 in Sønderborg, Denmark. They were soon thereafter demolished. One of the houses was timber build and from the late 16th century, while the other house was from around 1800. In advance of a new construction project on the address Museum Sønderjylland – Arkæologi excavated a 236 m² area at the site in 2021. The excavation resulted in the findings of five older phases of buildings: the oldest phase from the 14th century and the last phase from the 16th century. The oldest building was built with earth fast posts. From around 1400 it changed to a timber-framed construction on a stone foundation wall. The different phases had approximately the same placement, and orientation throughout the period. Moreover, some of the internal organisation in each house could be identified. Perlegade has been the main thoroughfare throughout Sønderborg’s history from around 1300 to modern time. The results not only contributed to the knowledge of the oldest house types in Sønderborg, but it also provided evidence that Perlegade and therefore also Sønderborg city extended north all the way to Perlegade 21 in the 14th century. This paper is a preliminary presentation of the results of the excavation.